Anion⋅⋅⋅Anion Coinage Bonds: The Case of Tetrachloridoaurate. (19th May 2021) - Daolio, Andrea; Pizzi, Andrea; Terraneo, Giancarlo; Ursini, Maurizio; Frontera, Antonio; Resnati, Giuseppe
Abstract: Interactions in crystalline tetrachloridoaurates of acetylcholine and dimethylpropiothetine are characterized by Au⋅⋅⋅ Cl and Au⋅⋅⋅ O short contacts. The former interactions assemble the AuCl4 − units into supramolecular anionic polymers, while the latter interactions append the acetylcholine and propiothetine units to the polymer. The distorted octahedral geometry of the bonding pattern around the gold center is rationalized on the basis of the anisotropic distribution of the electron density, which enables gold to behave as an electrophile (π‐hole coinage‐bond donor). Computational studies prove that gold atoms in negatively charged species can function as acceptors of electron density. The attractive nature of the Au⋅⋅⋅ Cl/O interactions described here complement the known aurophilic bonds involved in gold‐centered interactions. Abstract : The gold atom of the AuCl4 − moiety forms attractive anion⋅⋅⋅ anion and anion⋅⋅⋅ neutral electron–donor interactions. These interactions are rationalized as π‐hole coinage bonds and give rise to robust and reliable supramolecular synthons which control recognition and organization phenomena in the solid state. Hence, they might be considered for tuning structural and functional features in materials and biosystems.